Reconstruction of Pre-Trial Procedure Law Regulation Based on Justice Values - Sari, Pebrina Permata; Wahyuningsih, Sri Endah; Bawono, Bambang Tri; Mashdurohatun, Anis (Budapest International Research and Critics University, 2025)
The purpose of this study is to analyze and find related to pre-trial procedural law regulations that are not yet based on justice values, to analyze and find weaknesses in current pre-trial procedural law regulations, and to find a reconstruction of pre-trial procedural law regulations based on Justice Values. There are 3 (three) theories used, namely the Pancasila justice theory as a grand theory, the legal system theory as a middle theory, and the progressive legal theory as an applied theory. This research method uses a socio-legal approach method that law is both a norm and a behavior that examines social phenomena. The analysis of research data is descriptive qualitative. The location of the research was conducted at the Kuala Kapuas District Court. The data source is from the Judge at the Kuala Kapuas District Court.